Placebo Devices as Effective Control Methods in Acupuncture Clinical Trials: A Systematic Review. - Claire Shuiqing Zhang; Hsiewe Ying Tan; George Shengxi Zhang; Anthony Lin Zhang; Charlie Changli Xue; Yi Min Xie (PLoS ONE, 2015)
While the use of acupuncture has been recognised by the World Health Organisation, its efficacy for many of the common clinical conditions is still undergoing validation through randomised controlled trials (RCTs). A credible placebo control for such RCTs to enable meaningful evaluation of its efficacy is to be established. While several non-penetrating acupuncture placebo devices, namely the Streitberger, the Park and the Takakura Devices, have been developed and used in RCTs, their suitability as inert placebo controls needs to be rigorously determined. This article systematically reviews these devices as placebo interventions. Electronic searches were conducted on four English and two Chinese databases from their inceptions to July 2014; hand searches of relevant references were also conducted. RCTs, in English or Chinese language, comparing acupuncture with one of the aforementioned devices as the control intervention on human participants with any clinical condition and evaluating clinically related outcomes were included. Thirty-six studies were included for qualitative analysis while 14 were in the meta-analysis. The meta-analysis does not support the notion of either the Streitberger or the Park Device being inert control interventions while none of the studies involving the Takakura Device was included in the meta-analysis. Sixteen studies reported the occurrence of adverse events, with no significant difference between verum and placebo acupuncture. Author-reported blinding credibility showed that participant blinding was successful in most cases; however, when blinding index was calculated, only one study, which utilised the Park Device, seemed to have an ideal blinding scenario. Although the blinding index could not be calculated for the Takakura Device, it was the only device reported to enable practitioner blinding. There are limitations with each of the placebo devices and more rigorous studies are needed to further evaluate their effects and blinding credibility.